An examination of the facilitatory role for environmental education of conservancies - Law-Jackson, Danielle (Rhodes University, Faculty of Education, Department of Education, 2000)
This study examines the possibilities within the conservancy movement for the facilitation of environmental education. By means of a case study approach, a conservancy in the Northern Cape and the conservancy movement within the Free State provinces are compared with a view to elucidating factors militating against and promoting the success of environmental education programmes. The current lack of research in isolated rural areas is discussed. Re-orientation of perspectives regarding the value of conservancy-based environmental education within governmental, academic and local circles is recommended.
Keywords: Environmental education; Nature conservation -- South Africa; Wildlife conservation -- South Africa; Conservation of natural resources -- South Africa